Health precautions while traveling after COVID-19 - Teitler Regev Sharon; Shosh Shahrabani (Journal of Tourism, Heritage & Services Marketing, 2021)
Purpose: The tourism industry needs to identify potential tourists’ planned behavior after COVID-19 and prepare accordingly. This study was conducted in Israel during the initial outbreak of COVID-19. This research focused on different types of precautionary measures used by the tourists and how perceived risk of getting sick with COVID-19 while traveling abroad as well as risk perceptions and attitudes about travel abroad might affect tourists’ intentions to adopt precautionary measures when planning future travel abroad.